THE EFFECT OF RAP STRATEGY ON THE STUDENTS' READING COMPREHENSION - Tomi Mandala Putra; Destri Wahyuningsih (Program Studi Pendidikan Bahasa Inggris, 2026)
This research investigated the effectiveness of the Read–Ask–Put (RAP) Strategy in improving students’ reading comprehension at grade X of SMAN 2 Rakit Kulim. This research was motivated by students’ difficulties in understanding texts, such as identifying main ideas, understanding supporting details, making inferences, and understanding vocabulary in context. This research used a quasi-experimental design by comparing an experimental class taught using RAP Strategy and a control class taught using conventional methods. The data were collected through reading comprehension pre-tests and post-tests and then analyzed using the Independent Samples T-Test. The findings showed a significant improvement in the experimental class, with the mean score increasing from 54.80 to 84.60, which was higher than the control class post-test mean score of 77.20. The statistical analysis produced a Sig. (2-tailed) value of 0.000, indicating that RAP Strategy had a significant effect on students’ reading comprehension. This research concluded that RAP Strategy not only improved students’ reading comprehension ability but also encouraged students to become more active and independent in the reading learning process. Therefore, English teachers are recommended to apply RAP Strategy as one of the teaching strategies to improve students’ reading comprehension.